Transepithelial Secretion of Mucosal IgM Mediated by Polymeric Immunoglobulin Receptor of Flounder (Paralichthys olivaceus): In-Vivo and In-Vitro Evidence - Sheng, Xiuzhen; Guo, Yuan; Zhu, Hui; Chai, Baihui; Tang, Xiaoqian; Xing, Jing; Chi, Heng; Zhan, Wenbin (Frontiers in Immunology, 2022)
Secretory immunoglobulin (SIg) is crucial for mucosal surface defenses, but the transepithelial secretion of SIg mediated by polymeric immunoglobulin receptor (pIgR) is not clarified in fish. We previously found that flounder (Paralichthys olivaceus) pIgR (fpIgR) and secretory IgM (SIgM) increased in gut mucus post-vaccination. Here, the fpIgR-positive signal was mainly observed in the intestinal epithelium, whereas the IgM-positive signal was mainly distributed in the lamina propria, before immunization. IgM signals increased in the lamina propria and then in the epithelium after immunization with inactivated Vibrio anguillarum, and co-localization between IgM and fpIgR in the epithelium was determined, while the presence of EdU+IgM+ cells in the lamina propria identified the proliferative B cells, revealing that the secretion and transepithelial transport of SIgM locally occurred in the gut of flounder. Subsequently, we established an in-vitro model of transfected MDCK cells that stably expressed the fpIgR. After a recombinant eukaryotic expression plasmid (pCIneoEGFP-fpIgR) was constructed and transfected into MDCK cells, stable expression of the fpIgR in transfected MDCK-fpIgR cells was confirmed, and the tightness and integrity of the polarized cell monolayers grown on Transwells were evaluated. Afterward, the serum IgM of flounder was purified as a binding ligand and placed in the lower compartment of Transwells. An 800-kDa protein band in the upper compartment was shown to be IgM- and fpIgR-positive, and IgM-positive fluorescence was seen in MDCK-fpIgR cells but not in MDCK-mock cells. Hence, the fpIgR helped polymeric IgM to pass across MDCK-fpIgR cells via transcytosis in a basolateral-to-apical fashion. These new findings provide a better understanding of the pathways shaping mucosal IgM responses and the local mucosal immune mechanisms in teleosts.